A combined antibody and DNA assay for EBV infection in children - Yang, Yulu; Zhu, Yafei (Frontiers in Pediatrics, 2022)
Objective This paper studied the Epstein–Barr virus (EBV) infection status and influencing factors among children using a combined detection of specific antibodies and DNA. Methods We retrospectively analyzed children who visited the Affiliated Hospital of Hangzhou Normal University from January 2019 to December 2020, and correlations between the social environment and clinical data were analyzed. Results The cumulative positive rates of specific antibody, DNA, and combined detection of EBV were 52.4%, 39.5%, and 54.0% (P = 0.001), respectively. The current infection rate was 15.7%, and the peak of infection occurred in the preschool group (P = 0.021). After adjusting for confounding factors, the number of siblings (OR = 1.550) and family members who smoke (OR = 1.524) were independent risk factors for EBV infection, whereas parents with a higher education level (OR = 0.493, OR = 0.316), longer breastfeeding time (OR = 0.578) and dedicated tableware (OR = 0.573) were independent protective factors. Conclusion A combination of antibody and DNA tests may be beneficial for the diagnosis of EBV infection. The EBV infection rate in children at our hospital was lower than the national average. Furthermore, the infection rate is closely related to the number of siblings, regardless of whether family members smoke, the status of parents' education, breastfeeding duration, and meal patterns. Overall, prevention measures should focus on the preschoolers.